Dakwah Inklusif: Strategi Pengembangan Diri Penyandang Tunanetra pada Yayasan Komunitas Sahabat Mata Semarang - Marfai, Athiqoh Zakiyah; Wulandari, Sauma; Mu’afa, Nahidh Ahfash; Defri, Takariani; Nur Lyansari, Kirana (UIN Raden Mas Said Surakarta, 2025)
Da'wah as an effort to introduce and strengthen faith and religious experience, also has an important role in helping blind people achieve their best potential in self-development. Yayasan Komunitas Sahabat Mata is an organization committed to providing coaching and guidance to blind people in terms of self-development. This study aims to analyze the da'wah strategy used by Yayasan Komunitas Sahabat Mata in self-development for blind people. The research method used is qualitative. Data were collected through interviews, observations both offline and online. The results of the study indicate that Yayasan Komunitas Sahabat Mata uses effective da'wah strategies in the self-development of blind people. These strategies include the use of braille media to convey da'wah messages, providing religious education tailored to the needs of blind people, forming discussion groups and religious studies, and empowering communities in carrying out da'wah in the community.